Programmes design for teachers’ professional development as a way of organizational development for the human’s capital of the university - Gilmeeva Rimma (SHS Web of Conferences, 2021)
The relevance of the article is caused due to the importance of teacher’s professionalism in achieving success of university’s educational activity, and quality of higher education which defines the need for teacher’s continuous professional growth in higher school according to the pedagogical career strategy. It is determined by teacher’s individual needs and abilities, as well as the inquiries of the university. The leading role in the complex of training materials for additional professional education belongs to additional programmes of teachers’ professional development. The purpose of the article is to design additional programmes for teachers’ professional development and to identify the criteria for their efficiency. Packages of modular-based programmes, stages for design of the program for teachers’ professional development, characteristics of modular-based educational programmes, groups of quality criteria for the additional program for teachers’ professional development and a matrix of an expert assessment of programmes for teachers’ professional development (online mode) within external expertise are presented in the article. The authors emphasize the special role of personnel’s potential in the system of additional professional education. The article is intended for scientists, teachers, experts of the system of additional professional education, post-graduate students and students.